ENERGY AND NATURAL RESOURCES IN THE ARGENTINA-CHINA RELATIONSHIP: INTERESTS, COOPERATION AND CHALLENGES - Bilmes, Julian (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
The aim of this article is to analyze the outstanding role that energy and natural resources play in the increasing relationship between China and Argentina to inquire what type of development is outlined. These topics have a central role in terms of the bilateral trade balance, investment, funding and around cooperation mechanisms, due to Argentine bet to build new export complexes and Chinese needs for its energy and supply security. Oil and gas, mining and different type of energy generation are analyzed: nuclear, hydroelectric, solar and wind, highlighting Chinese firms positioning as well as bilateral cooperation agreements, its obstacles and challenges